A Triangulation Study to Explore the Effects of the Pick 'n Pay Smart Shopper Programme on Customer Brand Loyalty - McCulloch, Jessica (The IIE, 2016)
The South African retail industry is highly competitive, so brand awareness, customer loyalty, customer retention and conversion is vital to the long-term sustainability of brands. Many organisations have implemented loyalty programmes to develop strong customer relationships leading to customer retention and thus a competitive advantage (Duffy, 1998). The strategic aim of loyalty programmes is to ensure strong CRM (Customer Relationship Marketing) with customers resulting in return business and re-purchasing (Dowling and Uncles, 1997). The purpose of this study is to explore the effects the Pick ‘n Pay Smart Shopper loyalty programme has on customer brand loyalty. Pick n Pay is one of the biggest players in the grocery retail sector in the South African market, with being the only other retailer besides Woolworths to have a loyalty programme. The Pick n Pay Smart Shopper loyalty programme consists of members earing points (1 point for every R1 spent) which can then be used to pay for products within Pick n Pay stores (Pick n Pay, 2016). The study uses a mixed-method research methodology. An online questionnaire was used to collect qualitative and quantitative data from the sample. The questionnaire was distributed across a Facebook Forum through the use of Google Forms. The questionnaire was constructed to gather findings and form conclusions pertaining to consumers’ perceptions and preferences as well as the effect that loyalty programmes have on their loyalty towards the Pick n Pay brand. The most significant insights from the research findings were that the Pick n Pay Smart Shopper loyalty programme does not seem to make customers more brand loyalty or change their perceptions of the brand. A commonality amongst respondents was that the Smart Shopper programme should be that of a tiered loyalty programme, whereby consumers receive more points per spend based on the level (Bronze, Silver, Gold, Platinum) they are on within the loyalty programme. In conclusion, this study contributes to the body of knowledge on the effects that the Pick n Pay Smart Shopper loyalty programme has on customers’ brand loyalty, which has been a previously unexplored topic of study in the South African market.
Keywords: Brand loyalty; Brand awareness